Synthesis of Symmetrical Dodeco‐6, 7‐diuloses. Issue 28 (15th June 2020) - Bayer, Marius; Stocker, Simon; Maichle‐Mössmer, Cäcilia; Ziegler, Thomas
Abstract : Dodeco‐6, 7‐diuloses represent a rare class of sugars and can be considered as anomerically linked di‐hexoses with two hemiacetal functions in the middle. Herein, the synthesis of three symmetrical dodeco‐6, 7‐diuloses ( gluco ‐ gluco, galacto ‐ galacto, manno ‐ manno ) is described. For their preparation four synthetic strategies were pursued, whose mutual key step, the connection of the anomeric centers, is particularly emphasized. Specifically, C–C bond forming methods are employed, such as a Grubbs metathesis, a stannyl glycal homocoupling reaction, a coupling of a sulfinyl glycal with a sugar lactone and a Ramberg–Bäcklund rearrangement. Since the ring closure via hemiacetal formation of the target compounds cannot be predicted, intensive NMR spectroscopic structure elucidation of the diuloses was performed. Abstract : Four different synthetic strategies towards dodeco‐6, 7‐diuloses, which are structurally related to naturally occurring Peltalosa, are presented. Furthermore, detailed NMR spectroscopic investigations of these felxible, bis‐hemiacetalic compounds indicate a tendency to form preferred isomers.